Thermo-mechanical stability of multi-scale-architectured thin-film-based solid oxide fuel cells assessed by thermal cycling tests - Noh, Ho-Sung; Yoon, Kyung Joong; Kim, Byung-Kook; Je, Hae-June; Lee, Hae-Weon; Lee, Jong-Ho; Son, Ji-Won (ELSEVIER SCIENCE BV, 2014)
The thermo-mechanical stability of a thin-film and nanostructure-based SOFC (TF-SOFC) is assessed by thermal cycling tests. An ultrathin bi-layer electrolyte composed of 150-nm-thick yttria-stabilized zirconia (YSZ) and 450-nm-thick gadolinia-doped ceria (GDC) is successfully built on a NiO-YSZ anode support the microstructure scale of which changes from gm to nm (multi-scale architecture). The concept of multi-scale architecture in the TF-SOFC not only enables the reliable implementation of thin-film electrolytes and nanostructured electrodes to improve the critical low-temperature performance of the SOFC but also secures the thermo-mechanical stability of TF-SOFC. Competent cell performance is obtained, including a peak power density about 1.4 W cm(-2) at 600 degrees C. The TF-SOFC survives 50 thermal cycle tests between 600 and 400 degrees C over 124 h without suffering a drastic failure. Although some cell output degradation is observed after the thermal cycling tests, the cell sustains a peak power density over 1 W cm(-2) at 600 degrees C, which indicates the superior thermo-mechanical stability of the multi-scale-architectured TF-SOFC. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: PULSED-LASER DEPOSITION; LA0.6SR0.4COO3-DELTA-CE0.9GD0.1O2-DELTA NANO-COMPOSITE; ZIRCONIA ELECTROLYTE; PERFORMANCE; SOFC; MEMBRANES; ANODE; FABRICATION; CATHODES